Acupuncture Versus Cognitive Behavioral Therapy for Insomnia in Cancer Survivors: A Randomized Clinical Trial. (9th April 2019) - Garland, Sheila N; Xie, Sharon X; DuHamel, Kate; Bao, Ting; Li, Qing; Barg, Frances K; Song, Sarah; Kantoff, Philip; Gehrman, Philip; Mao, Jun J
Abstract: Background: Insomnia is a common and debilitating disorder experienced by cancer survivors. Although cancer survivors express a preference for using nonpharmacological treatment to manage insomnia, the comparative effectiveness between acupuncture and Cognitive Behavioral Therapy for Insomnia (CBT-I) for this disorder is unknown. Methods: This randomized trial compared 8 weeks of acupuncture (n = 80) and CBT-I (n = 80) in cancer survivors. Acupuncture involved stimulating specific points on the body with needles. CBT-I included sleep restriction, stimulus control, cognitive restructuring, relaxation training, and education. We measured insomnia severity (primary outcome), pain, fatigue, mood, and quality of life posttreatment (8 weeks) with follow-up until 20 weeks. We used linear mixed-effects models for analyses. All statistical tests were two-sided. Results: The mean age was 61.5 years and 56.9% were women. CBT-I was more effective than acupuncture posttreatment ( P  < .001); however, both acupuncture and CBT-I produced clinically meaningful reductions in insomnia severity (acupuncture: −8.31 points, 95% confidence interval = −9.36 to −7.26; CBT-I: −10.91 points, 95% confidence interval = −11.97 to −9.85) and maintained improvements up to 20 weeks. Acupuncture was more effective for pain at the end of treatment; both groups had similar improvements in fatigue, mood, and quality of life and reduced prescription hypnotic medication use. CBT-I was more effective for those who were male ( P  < .001), white ( P  = .003), highly educated ( P  < .001), and had no pain at baseline ( P  < .001). Conclusions: Although both treatments produced meaningful and durable improvements, CBT-I was more effective and should be the first line of therapy. The relative differences in the comparative effectiveness between the two interventions for specific groups should be confirmed in future adequately powered trials to guide more tailored interventions for insomnia.